Cinnamate 4-hydroxylase (C4H) genes from leucaena leucocephala: a pulp yielding leguminous tree - Kumar, Santosh; Omer, Sumita; Patel, Krunal; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Leucaena leucocephala is a leguminous tree species accounting for one-fourth of raw material supplied to paper and pulp industry in India. Cinnamate 4-Hydroxylase (C4H, EC 1.14.13.11) is the second gene of phenylpropanoid pathway and a member of cytochrome P450 family. There is currently intense interest to alter or modify lignin content of L. leucocephala. Three highly similar C4H alleles of LlC4H1 gene were isolated and characterized. The alleles shared more than 98 % sequence identity at amino acid level to each other. Binding of partial promoter of another C4H gene LlC4H2, to varying amounts of crude nuclear proteins isolated from leaf and stem tissues of L. leucocephala formed two loose and one strong complex, respectively, suggesting that the abundance of proteins that bind with the partial C4H promoter is higher in stem tissue than in leaf tissue. Quantitative Real Time PCR study suggested that among tissues of same age, root tissues had highest level of C4H transcripts. Maximum transcript level was observed in 30 day old root tissue. Among the tissues investigated, C4H activity was highest in 60 day old root tissues. Tissue specific quantitative comparison of lignin from developing seedling stage to 1 year old tree stage indicated that Klason lignin increased in tissues with age.
Keywords: Cinnamate 4-Hydroxylase (C4H); Leucaena leucocephala; lignin; Phenylpropanoid

Effect of different arginine methylations on the thermodynamics of tat peptide binding to HIV-1 TAR RNA - Kumar, Santosh; Maiti, Souvik (Biochimie, 2013)
RNA-binding proteins are an important class of mediators that regulate cell function and differentiation. Methylation of arginine, a post-translational modification (PTM) found in these proteins, can modulate their function. Arginine can be monomethylated or dimethylated, depending on the type of methyl transferases involved. This paper describes a comparative study of the thermodynamics of unmodified and modified Tat peptide interaction with TAR RNA, where the peptide is methylated at epsilon (epsilon) and eta (eta) nitrogen atoms of guanidinium group of arginine side chain at position 52 or 53. The results indicate that monomethylation of arginine at epsilon (epsilon) nitrogen atom enhances binding affinity, owing to a more favourable enthalpy component which overrides the less favourable entropy change. In contrast, monomethylation of arginine residue at eta nitrogen results in reduced binding affinity originating exclusively from a less favourable enthalpy change leaving entropic component unaffected. However, in case of simultaneous methylation at epsilon and eta positions, the binding parameters remain almost unaffected, when compared to the unmodified peptide. In case of symmetric dimethylation at eta position the observed enthalpy change of the binding was found to be smaller than the values obtained for the unmodified peptide. Asymmetric dimethylation at eta position showed the most reduced binding affinities owing to less favourable enthalpy changes. These results provide insights that enable elucidation of the biological outcome of arginine methylation as PTMs that regulate protein function, and will contribute to our understanding of how these PTMs are established in vitro and in vivo. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: HIV-1; Post-translational modification; Protein methylation; RNA-protein interaction; Thermodynamics

Effect of N-acetylation and N-methylation of lysine residue of tat peptide on its interaction with HIV-1 TAR RNA - Kumar, Santosh; Maiti, Souvik (Plos One, 2013)
Post-translational modification (PTM) of RNA binding proteins (RBPs) play a very important role in determining their binding to cognate RNAs and therefore regulate the downstream effects. Lysine can undergo various PTMs and thereby contribute to the regulation of different cellular processes. It can be reversibly acetylated and methylated using a pool of respective enzymes, to act as a switch for controlling the binding efficiency of RBPs. Here we have delineated the thermodynamic and kinetic effects of N-acetylation and N-monomethylation of lysine on interaction between HIV-1 TAR RNA and its cognate binder Tat peptide (a model system). Our results indicate that acetylation of lysine 50 (K50), leads to eight-fold reduction in binding affinity, originating exclusively from entropy changes whereas, lysine 51 (K51) acetylation resulted only in three fold decrease with large enthalpy-entropy compensation. The measurement of kinetic parameters indicated major change (4.5 fold) in dissociation rate in case of K50 acetylation however, K51 acetylation showed similar effect on both association and dissociation rates. In contrast, lysine methylation did not affect the binding affinity of Tat peptide to TAR RNA at K50, nonetheless three fold enhancement in binding affinity was observed at K51 position. In spite of large enthalpy-entropy compensation, lysine methylation seems to have more pronounced position specific effect on the kinetic parameters. In case of K50 methylation, simultaneous increase was observed in the rate of association and dissociation leaving binding affinity unaffected. The increased binding affinity for methylated Tat at K51 stems from faster association rate with slightly slower dissociation rate.

Molecular-beacon-based screen for small molecule inhibitors of miRNA maturation - Bose, Debojit; Jayaraj, Gopal Gunanathan; Kumar, Santosh; Maiti, Souvik (ACS Chemical Biology, 2013)
miRNAs are small non-coding RNAs that regulate about 60% of mammalian genes by modulating their transcript levels. Network scale studies of miRNA-mediated regulatory circuits demonstrate the central importance of this class of small RNA in the maintenance of biological robustness. More recently, several reports have described the deregulation of numerous miRNA to be causally associated with many diseases, including cancer. These studies have highlighted the potential for development of therapeutic modalities against miRNA. Previous screening protocols, for small molecules targeting miRNA function, are either costly or technically too complex to be applied in a high-throughput manner in standard chemical laboratories. We describe a simple in vitro screening method using a DNA-based molecular beacon that overcomes the limitations associated with earlier screens. We used this method to identify inhibitors of miR-27a function from a library of 14 aminoglycosides as a pilot study. Inhibitory molecules identified were further scrutinized to identify the validity of screen. With this proof of concept we illustrate the utility of a scalable molecular-beacon-based screening strategy for miRNA inhibitors.

One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Over-expression of a subgroup 4 R2R3 type MYB transcription factor gene from Leucaena leucocephala reduces lignin content in transgenic tobacco - Omer, Sumita; Kumar, Santosh; Khan, Bashir Mohammad (Plant Cell Reports, 2013)
LlMYB1 , a subgroup 4 R2R3-type MYB transcription factor gene from Leucaena leucocephala appears to be a repressor of lignin biosynthesis pathway by regulating the transcription of general phenylpropanoid pathway genes. R2R3MYB transcription factors are known to play a wide role in regulating the phenylpropanoid pathway in plants. In this study, we report isolation, cloning and characterization of an R2R3MYB transcription factor gene (LlMYB1) from an economically important tree species, Leucaena leucocephala. LlMYB1 consists of 705 bp coding sequence corresponding to 235 amino acids. Sequence alignment revealed that the N-terminal (MYB) domain of the gene shares up to 95 % similarity with subgroup 4 (Sg4) members of R2R3Myb gene family functionally known to be lignin repressors. Highly divergent C-terminal region of the gene carried an ERF-associated amphiphilic repression (EAR) motif, another characteristic of the Sg4. The gene was phylogenetically grouped closest with AmMYB308, a known repressor of monolignol biosynthetic pathway genes. Spatio-temporal expression studies at different ages of seedlings using quantitative real-time PCR (QRT-PCR) showed highest transcript level of the gene in 10 day old stem tissues. Over-expression of the gene in transgenic tobacco showed statistically significant decline in the transcript levels of the general phenylpropanoid pathway genes and reduction in lignin content. Our study suggests that LlMYB1 might be playing the role of a repressor of lignin biosynthesis in L. leucocephala.
Keywords: Leucaena leucocephala; lignin; R2R3MYB; Repressor; Transcript level

Thermodynamics and solvation dynamics of BIV TAR RNA-Tat peptide interaction - Goel, Teena; Kumar, Santosh; Maiti, Souvik (Molecular Biosystems, 2013)
The interaction of the trans-activation responsive (TAR) region of bovine immunodeficiency virus (BIV) RNA with the Tat peptide is known to play important role in viral replication. Despite being thoroughly studied through a structural point of view, the nature of binding between BIV TAR RNA and the BIV Tat peptide requires information related to its thermodynamics and the nature of hydration around the TAR-Tat complex. In this context, we carried out the thermodynamic study of binding of the Tat peptide to the BIV TAR RNA hairpin through different calorimetric and spectroscopic measurements. Fluorescence titration of 2-aminopurine tagged BIV TAR RNA with the Tat peptide gives their binding affinity. The isothermal titration calorimetric experiment reveals the enthalpy of binding between BIV TAR RNA and the Tat peptide to be largely exothermic with the value of -11.7 (SEM 0.2) kcal mol(-1). Solvation dynamics measurements of BIV TAR RNA having 2-AP located at the bulge region have been carried out in the absence and presence of the BIV Tat peptide using the time correlated single photon counting technique. The solvent cage around the Tat binding site of RNA appears to be more rigid in the presence of the Tat peptide as compared to the free RNA. The displacement of solvent and ions on RNA due to peptide binding influences the entropic contributions to the total binding energy.

In the sense of transcription regulation by G-quadruplexes: asymmetric effects in sense and antisense strands - Agarwal, Tani; Roy, Saumya; Kumar, Santosh; Chakraborty, Tushar Kanti; Maiti, Souvik (Biochemistry, 2014)
G-Quadruplexes occupy important regulatory regions in the genome. DNA G-quadruplexes in the promoter regions and RNA quadruplexes in the UTRs (untranslated regions) have been individually studied and variously implicated at different regulatory levels of gene expression. However, the formation of G-quadruplexes in the sense and antisense strands and their corresponding roles in gene regulation have not been studied in much detail. In the present study, we have elucidated the effect of strand asymmetry in this context. Using biophysical methods, we have demonstrated the formation of stable G-quadruplex structure in vitro using CD and UV melting. Additionally, ITC was employed to demonstrate that a previously reported selective G-quadruplex ligand was able to bind and stabilize the G-quadruplex in the present sequence. Further, we have shown using reporter constructs that although the DNA G-quadruplex in either strand can reduce translation efficiency, transcriptional regulation differs when G-quadruplex is present in the sense or antisense strand. We demonstrate that the G-quadruplex motif in the antisense strand substantially inhibits transcription, while when in the sense strand, it does not affect transcription, although it does ultimately reduce translation. Further, it is also shown that the G-quadruplex stabilizing ligand can enhance this asymmetric transcription regulation as a result of the increased stabilization of the G-quadruplex.

Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.

Understanding the effect of locked nucleic acid and 2 `-O-methyl modification on the hybridization thermodynamics of a miRNA-mRNA pair in the presence and absence of AfPiwi protein - Kumar, Santosh; Mapa, Koyeli; Maiti, Souvik (Biochemistry, 2014)
miRNAs are some of the key epigenetic regulators of gene expression. They act through hybridization with their target mRNA and modulate the level of respective proteins via different mechanisms. Various cancer conditions are known to be associated with up- and downregulation of the oncogenic and tumor suppressor miRNAs, respectively. The levels of aberrantly expressed oncogenic miRNAs can be downregulated in different ways. Similarly, restoration of tumor suppressor miRNAs to their normal levels can be achieved using miRNA mimics. However, the use of miRNA mimics is limited by their reduced biostability and function. We have studied the hybridization thermodynamics of the miRNA 26a (11-mer, including the seed sequence) guide strand with the mRNA (11-mer) target strand in the absence and presence of AfPiwi protein. We have also inserted locked nucleic acids (LNAs) and 2'-O-methyl-modified nucleotides into the guide strand, in a walk-through manner, to assess their effect on the binding efficiency between guide and target RNA. Insertion of LNA and 2'-O-methyl-modified nucleotides into the guide strand helped to strengthen the binding affinity irrespective of the position of insertion. However, in the presence of AfPiwi protein, these modifications reduced the binding affinity to different extents depending on the position of insertion. Insertion of a modification leads to an increase in the enthalpic contribution with an increased unfavorable entropic contribution, which negatively compensates for the higher favorable enthalpy.

Analyzing different acetyl co-a metabolizing enzymes as potential drug targets against mycobacterium tuberculosis - Akhtar, Shamim; Singh, Sheetal; Kumar, Santosh; Sarkar, Dhiman (British Microbiology Research Journal, 2015)
Mycobacterium tuberculosis, the causative agent of tuberculosis, is responsible for the deaths of million people around the globe. The scenario is worse than ever due to the emergence of drug resistant strains which are widely spread throughout the globe in much faster ways. To control this worst situation, we need to speed up the search for novel drugs which can specifically kill drug resistant bacteria in collaborative ways amongst academic, clinician and industry. Among different metabolic pathways, fatty acid synthesis pathway has always been a very attractive area for the drug target because of its crucial role during the infection and further in long term survival of pathogen inside the human host. In this review article, we analyzed the role of important and crucial enzymes, which are responsible for the influx and efflux of acetyl co-A substrate, a central hub of metabolites, as potential drug targets against M. tuberculosis.

Human telomeric RNA G-quadruplex response to point mutation in the G-quartets - Agarwala, Prachi; Kumar, Santosh; Pandey, Satyaprakash; Maiti, Souvik (Journal of Physical Chemistry B, 2015)
Many putative G-quadruplex forming sequences have been predicted to exist in the human genome and transcriptome. As these sequences are subject to point mutations or SNPs (single nucleotide polymorphisms) during the course of evolution, we attempt to understand impact of these mutations in context of RNA G-quadruplex formation using human telomeric RNA (TERRA) as a model sequence. Our studies suggest that G-quadruplex stability is sensitive to substitution of the guanines comprising G-quartets. While central G-quartet plays a crucial role in maintaining the DNA G-quadruplex stability as evident in literature, there is equal importance of three G-quartets in the stability of RNA quadruplex structure. The work here highlights the alterations in the G-quartet are detrimental to the integrity of overall RNA G-quadruplex structure. Furthermore, TmPyP4 molecules are shown to exhibit similar binding behavior toward telomeric RNA G-quadruplex harboring base substitutions employing CD titrations and isothermal titration calorimetry; well indicating that mutation does not influence TmPyP4 recognition ability as it affects the stability of RNA G-quadruplex. Thus, our study implicates that mutation in G-quartets causes destabilization of RNA G-quadruplex without affecting its trans factor binding ability.

Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.

G - C3N4 (2D)/CdS (1D)/rGO (2D) dual-interface nano-composite for excellent and stable visible light photocatalytic hydrogen generation - Tonda, Surendar (International Journal of Hydrogen Energy, 2017)
A 2D/1D/2D dual-interface nano-composite configuration in the form of CdS nanorods sandwiched between g-C3N4 and rGO sheets with intimate interfacial contact is synthesized by a facile wet-chemical method and is shown to exhibit excellent photocatalytic H2 generation under visible-light irradiation. In particular, the optimal g-C3N4/CdS/rGO dual-interface nano-composite shows H2 production rate of ∼4800 μmol h-1 g-1, which is almost 44, 11 and 2.5 times higher than that shown by pure g-C3N4 nanosheets, and the g-C3N4/rGO and g-C3N4/CdS single interface heterostructures, respectively. It is shown that the synergic effects involving the band structure match and close interfacial contact, which can accelerate the separation and transfer of photoinduced charge carriers, and the enhanced visible-light absorption together contribute to the impressive photocatalytic performance and photostability of the g-C3N4/CdS/rGO ternary nano-composite system. Specific advantages of a dual-interface triple-composite system over a single interface case(s) are also brought out.
Keywords: charge transfer; Dual Interface; G - CN; H Generation; Hetero Structure; Nano - Composite

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

G-C3N4/NiAl-LDH 2D/2D hybrid heterojunction for high-performance photocatalytic reduction ofco2 into renewable fuels - Tonda, Surendar; Kumar, Santosh; Bhardwaj, Monika; Yadav, Poonam; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2018)
2D/2D interface heterostructures of g-C3N4 and NiAl-LDH are synthesized utilizing strong electrostatic interactions between positively charged 2D NiAl-LDH sheets and negatively charged 2D g-C3N4 nanosheets. This new 2D/2D interface heterojunction showed remarkable performance for photocatalytic CO, reduction to produce renewable fuels such as CO and H-2 under visible-light irradiation, far superior to that of either single phase g-C3N4 or NiAl-LDH nanosheets. The enhancement of photocatalytic activity could be attributed mainly to the excellent interfacial contact at the heterojunction of gC(3)N(4)/NiAl-LDH, which subsequently results in suppressed recombination, and improved transfer and separation of photogenerated charge carriers. In addition, the optimal g-C3N4/NiAl-LDH nanocomposite possessed high photostability after successive experimental runs with no obvious change in the production of CO from CO, reduction. Our findings regarding the design, fabrication and photophysical properties of 2D/2D heterostructure systems may find use in other photocatalytic applications including H-2 production and water purification.

In situ phase transformation synthesis of unique Janus Ag2O/Ag2CO3 heterojunction photocatalyst with improved photocatalytic properties - Jo, Wan-Kuen; Kumar, Santosh; Yadav, Poonam; Tonda, Surendar (Applied Surface Science, 2018)
Herein, Ag2O/Ag2CO3 nanocomposite with unique Janus morphology was synthesized by a facile ion-exchange followed by an in situ phase transformation method with precise control of its nucleation and growth processes. Contrary to conventional synthetic procedures of Janus architectures, the present Janus system was constructed without the need for surfactants or toxic chemicals. Most importantly, the visible-light-absorbing Janus Ag2O/Ag2CO3 nanocomposite exhibits a remarkable performance toward the degradation of Rhodamine B and 4-chlorophenol, far superior to that observed for bare Ag2CO3. The obvious enhancement of the photocatalytic performance of this nanocomposite is mainly attributed to the intimate Ag2O/Ag2CO3 interface created by its exceptional Janus architecture, which in turn allows for rapid charge transfer processes. Additionally, the Janus system exhibited a high photostability during recycling experiments with no significant change in the degradation activity. (C) 2018 Published by Elsevier B.V.

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding

Direct Z-scheme g-C3N4/FeWO4 nanocomposite for enhanced and selective photocatalytic CO2 reduction under visible light - Bhosale, Reshma; Jain, Srashti; Vinod, Chathakudath Prabhakaran; Kumar, Santosh; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2019)
Photocatalytic reduction of CO2 to renewable solar fuels is considered to be a promising strategy to simultaneously solve both global warming and energy crises. However, development of a superior photocatalytic system with high product selectivity for CO2 reduction under solar light is the prime requisite. Herein, a series of nature-inspired Z-scheme g C3N4/FeWO4 composites are prepared for higher performance and selective CO2 reduction to CO as solar fuel under solar light. The novel direct Z-scheme coupling of the visible light-active FeWO4 nanoparticles with C3N4 nanosheets is seen to exhibit excellent performance for CO production with a rate of 6 mu mol/g/h at an ambient temperature, almost 6 times higher compared to pristine C3N4 and 15 times higher than pristine FeWO4. More importantly, selectivity for CO is 100% over other carbon products from CO, reduction and more than 90% over. H-2 products from water splitting. Our results clearly demonstrate that the staggered band structure between FeWO4 and C3N4 reflecting the nature-inspired Z-scheme system not only favors superior spatial separation of the electron hole pair in g-C3N4/FeWO4 but also shows good reusability. The present work provides unprecedented insights for constructing the direct Z-scheme by mimicking the nature for high performance and selective photocatalytic CO2 reduction into solar fuels under solar light.
Keywords: C3N4; CO2 reduction; FeWO4; Photocatalysis; solar fuels; Z-scheme

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides